Trade Costs and Real Exchange Rate Volatility : The Role of Ricardian Comparative Advantage. (IMF Working Papers; Working Paper ;, 2005)
This paper examines the impact of trade costs on real exchange rate volatility. We incorporate a multi-country Ricardian model of trade, based on the work of Eaton and Kortum (2002), into a macroeconomic model to show how bilateral real exchange rate volatility depends on relative technological differences and trade costs. These differences highlight a new channel, in which the similarity of a pair of countries' set of suppliers of traded goods affects bilateral exchange rate volatility. We then test the importance of this channel using a large panel of cross-country data over 1970-97, and find strong evidence supporting the channel.